PERKEMBANGAN BAHASA PADA ANAK USIA DINI DALAM KONTEKS MULTIBAHASA - Jannah, Riadotul; Depalina, Syamsiah (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Language development is a crucial aspect of early childhood education, as it plays a central role in communication, self-expression, and cognitive formation. In the context of Indonesia's multilingual society, children are often exposed to more than one language from an early age, including their mother tongue, Indonesian, and foreign languages. This study employs a literature review method to explore the process of language development in multilingual settings. The findings reveal that multilingual children tend to develop greater cognitive flexibility, social awareness, and communicative adaptability. Language acquisition occurs through two main pathways: simultaneous and sequential bilingualism, and is influenced by the quality of interaction between the child and their environment. Concerns regarding delayed speech in multilingual children are not supported by evidence; in fact, they often exhibit stronger cognitive and linguistic abilities. The active involvement of parents and educators is essential in guiding children to ensure balanced language development that also supports their cultural identity.